Karakteristik Tegangan Tembus Arus Bolak Balik Pada Minyak Jarak Pagar (Jatropha curcas) Sebagai Alternatif Isolasi Cair - Rendy Kamerlisa Putra; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Oil insulation generally use mineral oil because it has good heat absorption and dielectric characteristics as an insulator. Because of mineral oil is less friendly environmental, so important to find a solution to overcome them. This research aims to determine the feasibility of Jatropha curcas oil as an alternative oil insulation. This study has used variations of gap and water content to determine the effect on the breakdown voltage. The test result of the breakdown voltage of Jatropha curcas oil is compared to the breakdown voltage of the Shell Diala S2 ZU-1 oil. Futhermore the final result is found that the average of the breakdown voltage of Jatropha curcas is higher than Shell Diala S2 ZU-1 oil. The end of this study has achieved average values of breakdown voltage with lesser water concentration i.e. 2,17 %, 1,96%, 1,86%, etc. Prerequirements of the oil insulation must be agreed with the following standards i.e SPLN 49-91: 1982 and IEC 60296-2003. It’s explained that water concentrationt must fulfilled less than 3% (30 mg/kg). In this research Jatropha curcas oil have water concentration which complied to IEC 60296-2003 standard. SPLN 49-91: 1982 has declared that oil insulation must require the value of flash point ≥ 140°C, viscosity ≤ 40 cSt, pour point ≤ -30 °C, and density ≥ 0,859 gr/cm3. The result from this research should be fulfilled the caracteristic of breakdown voltage, flash point and water concentration that Jatropha curcas oil.Keywords: Oil insulation,breakdown voltage, jatropha oil.